STRATEGI COLLABORATIVE GOVERNANCE DALAM IMPLEMENTASI KEBIJAKAN LINK AND MATCH JENJANG SEKOLAH MENEGAH KEJURUAN DENGAN DUNIA USAHA/DUNIA INDUSTRI (DU/DI) DI KOTA BANDUNG (Studi Kasus di SMK Pasundan 1 Bandung) - Novie Permatasari; Edah Jubaedah (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2026)
Vocational High School has the goal of preparing a workforce that is ready to work as well as skilled. However, this is still a challenge because it is seen from the aspects of initial conditions, institutional design, facilitative leadership, collaboration processes that include face-to-face dialogue, building trust, and mutual understanding that have not been optimally implemented. This study aims to analyze the implementation of the Link and Match policy with the Business World/Industrial World (DU/DI) at SMK Pasundan 1 Bandung, identify the obstacles faced and formulate strategies in the implementation of collaborative governance. This study uses a qualitative descriptive method with a case study approach. Data collection through interviews, documentation and observation. The results of the study show that the implementation of the Link and Match policy between schools and DU/DI is still hampered by the misalignment of perceptions in understanding the policies implemented in vocational schools, then the synchronization between the school curriculum and DU/DI, then reluctant to be formally tied to the school, the competencies possessed by students and the active participation of stakeholders in the formulation of the vocational curriculum are not fully optimal. A strategy is needed in the form of utilizing the support of the principal together with the management team and teachers in forming a skilled workforce, harmonizing the synchronized curriculum and improving and maintaining a commitment to collaboration from the school in supporting the implementation of the link and match policy with DU/DI.